2015
DOI: 10.1007/s00464-015-4430-4
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of laparoscopic liver resection with associated lymphadenectomy for intrahepatic cholangiocarcinoma: a propensity score-based case-matched analysis from a single institution

Abstract: Compared with open surgery, laparoscopic resection of ICC is feasible and safe, providing short-term benefits without negatively affecting oncologic adequacy in terms of rate of R0 resections, depth of margins, and long-term overall and disease-free survivals. Laparoscopic regional lymphadenectomy is technically possible but should be the object of future focused studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 36 publications
4
48
0
5
Order By: Relevance
“…Regarding oncologic outcomes, there was no significant difference on R0 resection rates (OR, 0.71; 95% CI (0.07, 7.13); P = .77; heterogeneity, I 2 = 0%; Figure B), the findings are detailed in Table . Patients submitted to OLR had lymphadenectomy performed more frequently (OR, 0.09; 95% CI [0.04, 0.24]; P = 0 < 00001; heterogeneity, I 2 = 57%) (Figure C), and two studies reported number of harvested lymph nodes; pooled analysis data has shown that patients in LLR group had significantly lower number of harvested lymph nodes (OR, 0.46; 95% CI [−0.87, −0.06]; P = .03/heterogeneity I 2 = 0%) (Figure D). Also, there was no significant difference in 3‐year DFS between OLR and LLR (OR: 0.48, 95% CI: 0.2‐1.15 P = .1/heterogeneity I 2 = 0%; Figure E) and 3‐year OS (OR, 0.57; 95% CI, 0.22‐1.474; P = .24; heterogeneity I 2 = 0%; Figure F)…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Regarding oncologic outcomes, there was no significant difference on R0 resection rates (OR, 0.71; 95% CI (0.07, 7.13); P = .77; heterogeneity, I 2 = 0%; Figure B), the findings are detailed in Table . Patients submitted to OLR had lymphadenectomy performed more frequently (OR, 0.09; 95% CI [0.04, 0.24]; P = 0 < 00001; heterogeneity, I 2 = 57%) (Figure C), and two studies reported number of harvested lymph nodes; pooled analysis data has shown that patients in LLR group had significantly lower number of harvested lymph nodes (OR, 0.46; 95% CI [−0.87, −0.06]; P = .03/heterogeneity I 2 = 0%) (Figure D). Also, there was no significant difference in 3‐year DFS between OLR and LLR (OR: 0.48, 95% CI: 0.2‐1.15 P = .1/heterogeneity I 2 = 0%; Figure E) and 3‐year OS (OR, 0.57; 95% CI, 0.22‐1.474; P = .24; heterogeneity I 2 = 0%; Figure F)…”
Section: Resultsmentioning
confidence: 95%
“…Among 186 patients from four comparative studies with intrahepatic cholangiocarcinoma, 57 patients were submitted to LLR and 129 to OLR, as described in Table . Pooled data analyses concerning intra and postoperative outcomes are depicted in Figures and .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations